PENGARUH IKLAN OBAT FLU DI TELEVISI TERHADAP PEMILIHAN OBAT SECARA SWAMEDIKASI PADA MASYARAKAT DI MALANG - Hidajah Rachmawati (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2011)
Communications is process transfer of information signing the forwarding of message of someone to others, either through indirect and also direct that is media.Television as a mass media technically capable of informing public in numerous amount in the same time. One of television program offering various product to fulfill requirement and satisfaction of physical is commercial. Such commercial is influenza drug commercial, because met many people. This matter of tendency make people to do self-medication as solving of from problem of health which they recognize by self. Data collecting uses purposive sampling method in 102 respondents . Instrument test is done by validity test and reliability testing . Data analysis tool used is correlation analysis,t-test and regression analysis. Based on the result of the research, correlation coefficient is 0.645 so r table is 0,195, means there is a relation between influenza drug commercial and self-medication drug of choice. Based on the test t, t calculation is 2,376 so t table is 1,980, means there is influenza drug commercial in television has significant effect to self-medication drug of choice with equation regression Y = 4.803 + 0.522 x, means if influenza drug commercial in television indicator increasing 1 so self-medication drug of choice increasing 0.522. Value Sig. Of 0.000 <0.05 then the correlation coefficient deduced influenza drug commercial to self medication ‘s drug of choice in people in Malang is significant.